Efecto de los factores climáticos en la propagación del dengue, zika y chikunguña, transmitidas por mosquitos Aedes spp. en Sudamérica: Una revisión sistemática - Herrera Serrano, Geovanna Elizabeth (2025)
The high incidence of diseases transmitted by Aedes spp. mosquitoes, such as dengue, zika and chikungunya, has severely impacted public health in South America, where tropical and subtropical climates favor the proliferation of these vectors. This systematic review compiled information to understand the influence of climatic factors on the spread of these diseases in the region, with emphasis on variations in temperature, precipitation, and humidity. We analyzed studies published between 2019 and 2024 in all languages, which showed how climate change has altered seasonal patterns and expanded the optimal zones for mosquito breeding in South America. The results show that climatic factors such as high temperatures and seasonal rains have increased the activity and distribution of vectors, especially Aedes aegypti. The research highlights the need to improve control and epidemiological surveillance strategies, which must be adapted to climatic changes. Current interventions, such as the use of mosquito nets and spraying, have been insufficient in the face of the growth of risk areas. In addition, significant gaps were identified in research on other climatic factors and their interaction with the biological processes of viruses. This work emphasizes the importance of integrating climate variables into public health policies to design more effective control measures. The review also points out the importance of continuing to evaluate the effects of climate change on the spread of arbovirosis in order to strengthen the capacity to respond to future outbreaks and contribute to global efforts to reduce the burden of vector-borne diseases in the region